Anti‐citrullinated glucose‐6‐phosphate isomerase peptide antibodies in patients with rheumatoid arthritis are associated with HLA‐DRB1 shared epitope alleles and disease activity. (11th March 2013) - Umeda, N.; Matsumoto, I.; Ito, I.; Kawasaki, A.; Tanaka, Y.; Inoue, A.; Tsuboi, H.; Suzuki, T.; Hayashi, T.; Ito, S.; Tsuchiya, N.; Sumida, T.
Summary To identify and characterize anti‐citrullinated glucose‐6‐phosphate isomerase (GPI) peptide antibodies in patients with rheumatoid arthritis (RA). Nine GPI arginine‐bearing peptides in human GPI protein were selected and cyclic citrullinated GPI peptides (CCG‐1–9) were constructed. Samples were obtained from RA (n = 208), systemic lupus erythematosus (SLE) (n = 101), Sjögren's syndrome (SS; n = 101) and healthy controls (n = 174). Antibodies against CCG‐1–9 were measured, and anti‐citrullinated α‐enolase‐1 (CEP‐1), ‐cyclic citrullinated peptides (CCP) and ‐GPI proteins antibodies were also examined. Patients with RA were genotyped for HLA‐DRB1. The numbers of shared epitope (SE) alleles were counted and compared with those of the autoantibodies. Rabbit GPI was citrullinated with rabbit peptidylarginine deiminase and immunoblot analysis of RA sera performed. The levels of autoantibodies were compared before and after treatment with TNF antagonists in 58 RA patients. Anti‐CCG‐2, ‐4 and ‐7 antibodies were detected in 25·5, 33·2 and 37·0% patients with RA, respectively, and these antibodies were very specific for RA (specificity, 98·1–99·7%). Altogether, 44·2, 86·1 and 13·9% of RA sera were positive for anti‐CEP‐1, ‐CCP and ‐GPI protein antibodies, respectively. Anti‐CCG‐2, ‐4 and ‐7 antibodies were correlated with anti‐CCP and anti‐CEP‐1 antibodies and with the presence of HLA‐DRB1 SE alleles. Citrullinated GPI protein was detected using RA sera. Treatment with tumour necrosis factor antagonists reduced significantly the levels of anti‐CCG‐2 and ‐7 but not of anti‐CEP‐1 antibodies. This is the first report documenting the presence of anti‐CCG antibodies in RA. Anti‐CCG‐2 and ‐7 antibodies could be considered as markers for the diagnosis of RA and its disease activity.